2020
DOI: 10.1101/2020.07.10.151902
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of bioactive metabolites in human iPSC-derived dopaminergic neurons with PARK2 mutation: altered mitochondrial and energy metabolism

Abstract: PARK2 (parkin) mutations cause early onset of autosomal recessively inherited Parkinson's disease (PD). Parkin is an ubiquitin E3 ligase and has been reported to participate in several cellular functions, including mitochondrial homeostasis. However, the specific metabolomic changes caused by parkin depletion remain largely unknown. Human induced pluripotent stem cells (iPSCs) with PARK2 knockout (KO) provide a valuable model for studying parkin dysfunction in dopaminergic neurons. In the current study… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 81 publications
1
4
0
Order By: Relevance
“…PGC1‐α gene expression and protein deacetylation is regulated by the NAD + ‐dependent energy sensor SIRT1 28,29 . Moreover, our and a published metabolic study in parkin‐deficient neurons revealed increased lactate:pyruvate ratios, suggesting lower levels of freely accessible NAD + as a result of metabolic remodeling from oxidative phosphorylation to glycolysis 30,37 …”
Section: Discussionmentioning
confidence: 51%
“…PGC1‐α gene expression and protein deacetylation is regulated by the NAD + ‐dependent energy sensor SIRT1 28,29 . Moreover, our and a published metabolic study in parkin‐deficient neurons revealed increased lactate:pyruvate ratios, suggesting lower levels of freely accessible NAD + as a result of metabolic remodeling from oxidative phosphorylation to glycolysis 30,37 …”
Section: Discussionmentioning
confidence: 51%
“…12 Notably, a similar elevation in TCA intermediate metabolites was recently observed in PRKN KO iDA neurons, which also have an OXPHOS deficit and a low NAD + /NADH ratio. 11 This is consistent with an OXPHOS defect driving the low NAD + /NADH ratio as well as metabolites in NAD + -dependent reactions in the setting of PRKN deficiency.…”
supporting
confidence: 67%
“…Lowered NAD + suppresses PGC1-α signaling by decreasing the activity of SIRT1, an NAD +dependent deacetylase. 10 Although Wasner et al 8 do not directly measure NAD + and NADH, a recent study found that the NAD + /NADH ratio is decreased in PRKN KO and patient iDA neurons, 11 and both studies found an increase in the lactate/pyruvate ratio, 8,11 which is metabolically coupled to the NAD + /NADH ratio. Based on these findings, the authors suggest that Parkin deficiency may decrease mitochondrial biogenesis through lowered NAD + , via the SIRT1-PGC1-α/NRF1-TFAM signaling axis.…”
mentioning
confidence: 99%
“…In addition to structural differences, we identified alterations of the global transcriptome and metabolome in both MZ and ZZ iHeps, some of which have been previously associated with ER stress or mitochondrial dysfunction (35)(36)(37)42). Among these were enrichment for metabolites significant in the citric acid cycle, glutathione metabolism, and branched chain amino acid and tRNA biosynthesis.…”
Section: Discussionmentioning
confidence: 94%